2015
DOI: 10.1002/hep.28286
|View full text |Cite
|
Sign up to set email alerts
|

Akt‐mediated foxo1 inhibition is required for liver regeneration

Abstract: Understanding the hepatic regenerative process has clinical interest, since the effectiveness of many treatments for chronic liver diseases is conditioned by an efficient liver regeneration. Experimental evidence points to the need of a temporal coordination between cytokines, growth factors and metabolic signaling pathways to enable successful liver regeneration. One intracellular mediator that acts as a signal integration node for these processes is the serine-threonine kinase Akt/PKB (Akt). To investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
60
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 59 publications
7
60
0
Order By: Relevance
“…Transient hepatic steatosis is a characteristic feature of liver regeneration . In other experimental settings, Nampt has been suggested to confer resistance to hepatic steatosis through NAD synthesis, and it was recently shown that NR supplementation confers protection against steatosis in mice fed a high‐fat/high‐sucrose diet .…”
Section: Discussionmentioning
confidence: 99%
“…Transient hepatic steatosis is a characteristic feature of liver regeneration . In other experimental settings, Nampt has been suggested to confer resistance to hepatic steatosis through NAD synthesis, and it was recently shown that NR supplementation confers protection against steatosis in mice fed a high‐fat/high‐sucrose diet .…”
Section: Discussionmentioning
confidence: 99%
“…Rictor, interacting with mTOR, was also decreased in METKO+EGFRi mice. Recent studies have shown that AKT activity is essential for full liver regeneration, acting primarily through control and inhibition of Foxo1 . The reduced levels of Rictor–mTORC2 affected AKT activation.…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, PI3K seems to promote hyperplasia by phosphorylating signal transducer and activator of transcription 3 (STAT3), whereas the phosphoinositide‐dependent AKT‐mTOR axis stimulates hypertrophic growth . Notably, AKT signaling regulates many of the metabolic adaptations associated with regeneration after tissue loss . No direct evidence supports a role for PTEN in liver regeneration to date.…”
mentioning
confidence: 99%